1988
DOI: 10.1152/jappl.1988.65.5.2285
|View full text |Cite
|
Sign up to set email alerts
|

Potential for strength and endurance training to amplify endurance performance

Abstract: The impact of adding heavy-resistance training to increase leg-muscle strength was studied in eight cycling- and running-trained subjects who were already at a steady-state level of performance. Strength training was performed 3 days/wk for 10 wk, whereas endurance training remained constant during this phase. After 10 wk, leg strength was increased by an average of 30%, but thigh girth and biopsied vastus lateralis muscle fiber areas (fast and slow twitch) and citrate synthase activities were unchanged. Maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
175
5
19

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(230 citation statements)
references
References 16 publications
27
175
5
19
Order By: Relevance
“…It seems that training preparation primarily focused on the both speed-endurance and explosive strength may lead among others to the enhancement in the work economy. Our results are in agreement with the study of Hickson, Dvorak, Gorostiaga, Kurowski, and Foster (1988) who showed that an incorporation the strength drills into endurance program resulted in an increase of 13% in short-term endurance (time to exhaustion on the treadmill) together with unchanged VO 2 max level. On the other hand, Botek et al (2010) demonstrated a significant increase in VO 2 max after 5 weeks training in soccer players who performed both strength, and endurance drills.…”
Section: Discussionsupporting
confidence: 93%
“…It seems that training preparation primarily focused on the both speed-endurance and explosive strength may lead among others to the enhancement in the work economy. Our results are in agreement with the study of Hickson, Dvorak, Gorostiaga, Kurowski, and Foster (1988) who showed that an incorporation the strength drills into endurance program resulted in an increase of 13% in short-term endurance (time to exhaustion on the treadmill) together with unchanged VO 2 max level. On the other hand, Botek et al (2010) demonstrated a significant increase in VO 2 max after 5 weeks training in soccer players who performed both strength, and endurance drills.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies (17,36,43) have reported that various forms of resistance training may lead to improved endurance performance in trained subjects. However, the optimal prescription of resistance training to improve endurance running performance has yet to be firmly established.…”
Section: Discussionmentioning
confidence: 98%
“…71 Table 1. Training Recommendations HIIT 1-3 sessions per week; interval durations up to 60%Tlim, total of ≈ 10 mins close to vVO2max ; use no-impact modes for additional training volume for overweight individuals 41,45,50,57 Distance Training 0-4 sessions per week; 12-40 mins in duration, 60-80% HRmax 29,55,68 Plyometrics/Mechanics Drills 2 sessions per week: 5-10 sprints of 20-100m, 30-200 foot contacts, 5-20 repetitions per set, loads 0-40% 1RM 29,72 Strength Training 2-10 exercises; 2-5 sessions per week; ≥3 sets of multiple joint exercises at intensities from 12RM to 3RM (≈ 70-95% 1RM); periodized program; 27,28,32,62,70,72,73 …”
Section: Discussionmentioning
confidence: 99%
“…25 A variety of strength training programs using heavy loads and lighter loads in explosive strength training have been shown to improve running performance in middle distances and laboratory runs within our target timeframes with subjects from a variety of populations. [26][27][28] No studies were available that evaluated chronic strength training programs (beyond 28 weeks) in distance runners. However, evidence indicates that strength training can improve run performance.…”
Section: Strengthmentioning
confidence: 99%